PROGNOSTICATION OF SUCCESSFULNESS IN ARM-WRESTLING ON THE BASE OF MORPHOLOGICAL FUNCTIONAL INDICATORS’ ANALYSIS - L.V. Podrigalo; M. N. Galashko; S.S. Iermakov; O.A. Rovnaya; A.Y. Bulashev (Physical Education of Students)
Purpose: to work out methodic of arm wrestling successfulness prognostication by morphological functional indicators and substantiate it. Material: 189 sportsmen (of age 21.62 +- 0.85 years) were tested. We fulfilled goniometric testing of arms’ joints (n=27) and hand dynamometry (n=50). Characteristics of physiological tremor were studied (n=29). Strength of forearm’s muscles was determined (n=33) as well as the strength of hand fingers’ extensors separately (n=50). Prognostication was realized with the help of sequential procedure by Wald’s methodic, with calculation of prognostic coefficients and their informative potential. Results: prognostic table, containing functional state indicators of arm-wrestlers. It contained 18 criteria. The criteria illustrate power, goniometric and functional indicators. Informative potential varied within 64.70 - 6.33. The sense of prognosis is assessment of results and determination of appropriate prognostic coefficient. Besides, prognosis implies summing up of these coefficients for achievement of one of prognostic thresholds. The value of these thresholds was determined at level of +- 13, that corresponds to 95% probability. Achievement of threshold + 13 and more means sportsman’s successfulness higher level. In case of lower threshold achievement successfulness probability is low. Conclusions: the conducted researches permitted to work out methodic of arm wrestling successfulness prognostication by morphological functional indicators and substantiate it. The offered methodic is based on sequential analysis by Wald and is a simple, informative and objective tool of arm-wrestlers’ condition control.